2020
DOI: 10.1038/s41591-020-0752-4
|View full text |Cite
|
Sign up to set email alerts
|

An immune-cell signature of bacterial sepsis

Abstract: Dysregulation of the immune response to bacterial infection can lead to sepsis, a condition with high mortality. Multiple whole-blood gene expression studies have defined sepsis-associated molecular signatures but did not resolve changes in transcriptional states of specific cell types. Here, we used single-cell RNA sequencing to profile the blood of patients with sepsis (n = 29) across three clinical cohorts with corresponding controls (n = 36). We profiled total peripheral blood mononuclear cells (PBMCs, 106… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

30
391
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 332 publications
(423 citation statements)
references
References 52 publications
30
391
1
1
Order By: Relevance
“…The accumulation of additional host-pathogen single-cell datasets promises to greatly enhance our understanding of infection by allowing us to determine which features of pathogenesis are shared between, or specific to, individual pathogens. For example, our scRNA-Seq and CyTOF data identified several molecular commonalities between EVD and immunosuppressive septic shock (Bray and Mahanty, 2003) , which is also characterized by loss of MHC-II expression in monocytes (Monneret and Venet, 2014;Reyes et al, 2020) , increased DP monocytes (Fingerle et al, 1993) , and emergency myelopoiesis (Bomans et al, 2018;Cuenca et al, 2015;Reyes et al, 2020) . Soluble mediators, including cytokines and glucocorticoids, could be key drivers of both EVD and sepsis pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of additional host-pathogen single-cell datasets promises to greatly enhance our understanding of infection by allowing us to determine which features of pathogenesis are shared between, or specific to, individual pathogens. For example, our scRNA-Seq and CyTOF data identified several molecular commonalities between EVD and immunosuppressive septic shock (Bray and Mahanty, 2003) , which is also characterized by loss of MHC-II expression in monocytes (Monneret and Venet, 2014;Reyes et al, 2020) , increased DP monocytes (Fingerle et al, 1993) , and emergency myelopoiesis (Bomans et al, 2018;Cuenca et al, 2015;Reyes et al, 2020) . Soluble mediators, including cytokines and glucocorticoids, could be key drivers of both EVD and sepsis pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…Immunoparalysis is likely the ground for the HSV-1 superinfection observed in some ICU patients in our study. Recently, scRNA-seq unveiled a cluster of immature CD14 + monocytes, with low HLA-DR and expressing MPO, PLAC8 and IL1R2, in the blood of COVID-19 patients and similar cells were reported in sepsis [20,33]. These ndings shed light on the practice to measure the levels of HLA-DR in monocytes as marker for sepsis, preconized but never de nitively proven as mortality biomarker for severe sepsis, especially in ICU patients [34,35].…”
Section: Discussionmentioning
confidence: 86%
“…More importantly, we found that loss of function in myeloid cells mirrors an immune pathological status progressing from immune paralysis to "immune silence" associated with higher susceptibility to death event (Figure 2e, Figure S2f). CD14 + HLA-DR low monocytes and ARG1 + MPO + BPI +, low density pre-neutrophils are expanded in severe COVID-19 patients, a likely consequence of the pervasive emergency myelopoiesis triggered by SARS-Cov2 infection [33]. Based on gene expression pro les, these cell subsets were deemed to have immune suppressive features, which were not functionally addressed in the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Blériot et al, 2020;Nutt and Chopin, 2020). To perform these functions, these cell types execute diverse and distinct transcriptional programs in response to local and systemic cues (Jaitin et al, 2019;Maier et al, 2020;Okabe and Medzhitov, 2016;Reyes et al, 2020). This transcriptional diversity has been particularly appreciated in macrophages, where the classically-defined dichotomous spectrum has been progressively expanded in favor of a complex spectrum both in vitro and in vivo (Gautier et al, 2012;Li et al, 2019;Rajab et al, 2019;Sica and Mantovani, 2012;Xue et al, 2014).…”
Section: Introductionmentioning
confidence: 99%